The Development of Students Worksheet Based on Science Literacy in Environmental Pollution Material - Vony Nurul Fatma; Ani Rusilowati; Sigit Saptono (Universitas Negeri Semarang, 2023)
The aim of this study is to describe the characteristics, analyze the validity and readability of student’s worksheet (LKPD) on environmental pollution material for junior high school. This type of research was a Research and Development (R&D). Development research using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This development was limited to the development stage. The practically instrument was a questionnaire of teacher and students. The validator consists of media expert and material expert. The data obtained is qualitative data converted to quantitative data. The result showed that the validity by media expert obtained high validity criteria with an average score of 94.7 and an average score by material expert of 84.5 obtained a high valid criterion. The readability test of student’s worksheet was tested on limited students with 10 students of class VIII SMP Negeri 1 Ngrampal and 1 science teacher. The result of the response of student obtained 92.5 with very good criteria. The result of teacher response obtained 91.98 with very good criteria. It can be concluded that the student’s worksheet develops feasible and practically used in the learning process.